Kiai's Leadership In Empowerment Of People (Case Study At Al-Hidayah Islamic Boarding School Cikalong Tasikmalaya) - Deni Permana; Ulfiah; Deti Rostini; Sayid M. Rifki Noval (IJGIE (International Journal of Graduate of Islamic Education), 2022)
The kiai's activities give rise to diverse views among the people. Several factors are behind the differences in views, including the leadership factor. One of the reasons for this gap between the kiai is the lack of awareness of the kiai in administrative matters in the organization, so that a new breakthrough is needed for the kiai, namely by making efforts to empower the people. This research is a qualitative research, a research that aims to reveal an event, phenomenon, activity, and perception of others in a certain social context. Socio-anthropological approach. Data collection techniques through interviews, observation, and documentation. The results of the study indicate that the kiai's leadership is based on social aspects including the legal-formal leadership model, namely the form of policy must be in accordance with organizational mechanisms including administrative order. Religiously, the leadership of KH. Nurdin Alhusainy as a charismatic leader, encourages other kiai to master various types of disciplines so that they can be implemented in the current context. Second, in the aspect of empowering the people, socially advocating for the people regarding civilized social concepts and actions to criticize the rulers who are not in favor of the people. In addition, in the field of religion, encourage other kiai who are affiliated with religious organizations to open themselves in dealing with religious issues on social media scientifically, not in unwise and hateful ways.